The Benefits of Baby Gym on Development of Baby Age 6 Months - Siti Nur Umariyah Febriyanti; Difi Nurlintan; Rose Nur Hudhariani (JURNAL KEBIDANAN, 2020)
The World Health Organization (WHO) states that around 30% of infants experience mild developmental delays. Babies aged 0-12 months are a golden period as well as a critical period, because it lasts very short. Developmental problems start from gross motoric, subtle, speech and language skills and socialization and independence. Babies need proper nutrition and stimulation. Baby gym or baby gymnastics is one of the effective stimulations, as well as observing early detection of indications of developmental irregularities. Objective: To determine the effect of baby gym on the development of 6-month-old infants in the Pegandan health center in Semarang. Research Methods: The type of research used in this study was quasi experimental by using one group pre test - post test design. The sample used in this study amounted to 16 babies, sampling technique with accidental sampling, 3 time week until 4 weeks within 10 minuts. Results: The results of the study before the baby gym were median of 8.00, while after the baby gym the median value was 10.00. This study used the Wilcoxon statistical test with the results of p-value = 0,000 (0.05). Conclusion: There is a baby gym influence on the development of 6-month-old babies.